Dense‐map genome scan for dyslexia supports loci at 4q13, 16p12, 17q22; suggests novel locus at 7q36. (7th December 2012) - Field, L. L.; Shumansky, K.; Ryan, J.; Truong, D.; Swiergala, E.; Kaplan, B. J.
Abstract : Analysis of genetic linkage to dyslexia was performed using 133, 165 array‐based SNPs genotyped in 718 persons from 101 dyslexia‐affected families. Results showed five linkage peaks with lod scores >2.3 (4q13.1, 7q36.1‐q36.2, 7q36.3, 16p12.1, and 17q22). Of these five regions, three have been previously implicated in dyslexia (4q13.1, 16p12.1, and 17q22), three have been implicated in attention‐deficit hyperactivity disorder (ADHD, which highly co‐occurs with dyslexia; 4q13.1, 7q36.3, 16p12.1) and four have been implicated in autism (a condition characterized by language deficits; 7q36.1‐q36.2, 7q36.3, 16p12.1, and 17q22). These results highlight the reproducibility of dyslexia linkage signals, even without formally significant lod scores, and suggest dyslexia predisposing genes with relatively major effects and locus heterogeneity. The largest lod score (2.80) occurred at 17q22 within the MSI2 gene, involved in neuronal stem cell lineage proliferation. Interestingly, the 4q13.1 linkage peak (lod 2.34) occurred immediately upstream of the LPHN3 gene, recently reported both linked and associated with ADHD. Separate analyses of larger pedigrees revealed lods >2.3 at 1–3 regions per family; one family showed strong linkage (lod 2.9) to a known dyslexia locus (18p11) not detected in our overall data, demonstrating the value of analyzing single large pedigrees. Association analysis identified no SNPs with genome‐wide significance, although a borderline significant SNP ( P  = 6 × 10 –7 ) occurred at 5q35.1 near FGF18, involved in laminar positioning of cortical neurons during development. We conclude that dyslexia genes with relatively major effects exist, are detectable by linkage analysis despite genetic heterogeneity, and show substantial overlapping predisposition with ADHD and autism. Abstract : Family analysis using SNP arrays shows dyslexia linkage peak at 17q22 in MSI2 gene involved in proliferation of neuronal stem cell lineages.